A super weather-resistant antifouling coating and preparation method thereof
The mesoporous silica-loaded coating is formed by using modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane and mesoporous silica in ultraweather-resistant antifouling coatings, and The addition of epoxy resin solves the problem of insufficient anti-icing performance of the coating under extremely low temperature conditions, significantly improves multiple properties and extends its service life.
Patent Information
- Application Number
- CN202411126670.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-16
AI Technical Summary
Existing ultra-weather and antifouling coatings are difficult to maintain good anti-icing performance under extremely low temperature conditions.
Modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane and mesoporous silica are used to form a coating loaded with mesoporous silica through multiple steps. Epoxy resin is added to the coating to improve adhesion and mechanical strength.
Under extremely low temperature conditions of -20℃, the paint maintains structural integrity and functionality, significantly improves its resistance to icing, hydrophobicity, soil resistance, weather resistance and UV aging resistance, and extends the service life of the paint.
Smart Images

Figure BDA0004996613740000091 
Figure BDA0004996613740000101 
Figure BDA0004996613740000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antifouling coatings, and in particular to a super-weather-resistant antifouling coating and a preparation method thereof. Background Art
[0002] Super weather-resistant antifouling coating is a high-performance coating that can maintain stability and durability under extreme climatic conditions. It not only has excellent weather resistance, but also can effectively resist the attachment of various pollutants and withstand long-term wind, rain and extreme climatic conditions. Super weather-resistant antifouling coating is widely used in high-speed railways, bridges, petrochemical tanks and other surfaces that need to be exposed to harsh environments for a long time to reduce maintenance costs and improve cleaning efficiency, protect the structure from environmental factors such as humidity, temperature changes, chemical corrosion and ultraviolet radiation, thereby extending its service life and maintaining its appearance, including but not limited to anti-corrosion, anti-rust, weather resistance, wear resistance, anti-ultraviolet, self-cleaning and other performance characteristics. Improve anti-corrosion and anti-rust performance to further protect the substrate from corrosion and ensure the durability and durability of the coating; improve wear resistance to reduce wear caused by daily use and maintenance. Improve anti-fouling performance to facilitate maintenance and keep the appearance clean; have good UV resistance to prevent aging and fading caused by long-term exposure to sunlight; have self-cleaning properties to promote the shedding of dirt in rain or other natural conditions, and keep the surface clean and beautiful.
[0003] With the advancement of science and technology, the following technical solutions are usually used to improve the hydrophobic, anti-icing and anti-fouling properties of super-weather-resistant coatings: hydrophobicity can be improved by adding hydrophobic additives to the coating or using nanotechnology to increase micro-texture or low surface energy surface to reduce the adhesion of water molecules; anti-icing performance can be improved by adding chemicals that can lower the freezing point or using surface structure to interfere with ice formation, or by increasing hydrophobicity to reduce water adhesion, repel water droplets and ice crystals to prevent ice formation; anti-fouling performance can be improved by adding anti-fouling ingredients such as fluorides or silanes to reduce surface energy and reduce the adhesion of pollutants. By optimizing the formulation of the coating to improve its durability and resistance to chemical erosion, ensure that the coating can still maintain its hydrophobic, anti-icing and anti-fouling properties when exposed to harsh environmental conditions for a long time, improve the comprehensive performance of the coating, and make it more adaptable to various environmental challenges.
[0004] CN103059650A discloses a nano coating for preventing ice from forming on high-voltage transmission lines and its use. First, according to the weight percentage, 10% to 15% of polymer resin, 20% to 25% of titanium dioxide, 30% to 35% of silicon dioxide, and 3% to 5% of diamond-like carbon are weighed respectively; the solvent is 19% to 32%; then the polymer resin, titanium dioxide, silicon dioxide and diamond-like carbon compound are mixed and ground evenly to make the particle size of the particles 1 to 100nm, and finally the raw materials after mixing and grinding evenly are added to the solvent and stirred fully to obtain the nano coating for preventing ice from forming on high-voltage transmission lines. The coating of the invention enables high-voltage wires to have the advantages of anti-fouling, anti-icing and high wear resistance. It is a long-term, efficient, convenient, economical and feasible active anti-ice and snow disaster method, which can delay and prevent the ice from forming on the supercooled water droplets on the high-voltage transmission line, and the high-voltage line will not produce ice or produce a trace of ice in rainy and snowy weather. This invention patent adds diamond-like carbon to improve functionality, but diamond-like carbon has a high cost and is not suitable for large-area applications.
[0005] CN114635116A discloses a multi-level corrosion-resistant, anti-friction and anti-icing coating and its preparation method. The invention adopts femtosecond laser processing technology on the surface of the substrate to prepare a micron-level rough texture with a bionic structure, and then magnetron co-sputters TiAlCrNbZr alloy target and single-substance target Cu or / and Ag to form a TiAlCrNbZrCu or / and Ag corrosion-resistant film with a nano-level micro-convex structure, thereby forming a film of a micron-level and nano-level bionic multi-level composite structure. The bionic multi-level composite structure has good hydrophobicity, so that the droplets roll off the hydrophobic surface before freezing, preventing ice and dirt adhesion, and achieving anti-fouling and anti-icing; at the same time, the Cu and Ag elements distributed on the nano-micro-convex reduce the adhesion of microorganisms by the nano-micro-convex, and rely on the nano Cu and Ag elements to play a bactericidal role, so there are Cu or Ag elements and the bionic multi-level composite structure, which can synergistically improve the hydrophobicity, anti-fouling and anti-icing effects of the film layer. This invention patent uses magnetron sputtering technology to obtain a multi-level composite coating. The coating steps are complicated, have high requirements for process technology and equipment, and have limited practical application scope. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a super weather-resistant antifouling coating for use on the surface of high-speed railways, landscape bridges, and petrochemical tanks, which can ensure good anti-icing performance at -20°C.
[0007] To achieve the above object, the present invention provides a super weather-resistant antifouling coating and a preparation method thereof.
[0008] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0009] (1) adding molybdenum disulfide to an aqueous ammonia solution, stirring at room temperature for 1-2 hours to obtain a dispersion, adding γ-glycidyloxypropyltrimethoxysilane, stirring at 50-60° C. for 8-10 hours, filtering, and vacuum drying at 60-80° C. to obtain modified molybdenum disulfide;
[0010] (2) adding modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, dicyclohexylcarbodiimide, and phenyltrimethylammonium chloride to N,N-dimethylformamide, adding mesoporous silica, stirring at 120-140° C. for 12-24 hours, filtering, washing the filter cake with anhydrous ethanol for 2-4 times, and vacuum drying at 50-60° C. to obtain loaded mesoporous silica;
[0011] (3) adding epoxy resin, loaded mesoporous silica, defoaming agent and leveling agent to anhydrous ethanol in sequence, stirring at room temperature for 1-2 hours, adding curing agent, and ultrasonically dispersing for 10-30 minutes to obtain the super weather-resistant antifouling coating.
[0012] The ammonia solution in step (1) is a 20-25 wt % ammonia solution.
[0013] In the step (1), the weight ratio of molybdenum disulfide, ammonia solution and γ-glycidyloxypropyltrimethoxysilane is 2-3:20-30:0.4-0.6.
[0014] In the step (2), the weight ratio of modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, dicyclohexylcarbodiimide, phenyltrimethylammonium chloride, N,N-dimethylformamide, and mesoporous silica is 1-3: 3-6: 0.5-1: 0.2-0.6: 180-220: 180-220.
[0015] In the step (3), the weight ratio of epoxy resin, loaded mesoporous silica, defoamer, leveling agent, anhydrous ethanol and curing agent is 140-160:180-220:1-2:1-2:120-160:30-60.
[0016] The pore size of the mesoporous silica in step (2) is 1-5 nm.
[0017] The defoaming agent in step (3) is polydimethylsiloxane.
[0018] The leveling agent in step (3) is a polyether modified silicone leveling agent.
[0019] Epoxy resin has excellent adhesion, mechanical strength and chemical corrosion resistance. It is the main film-forming substance in the coating. The three-dimensional network structure formed after curing provides the coating with extremely high cohesion and adhesion, ensuring that the coating can adhere tightly to the surface of objects such as high-speed railways, landscape bridges, and petrochemical tanks, and can remain stable even in harsh outdoor environments. Epoxy resin has a high glass transition temperature, which allows the coating to maintain a certain flexibility and ductility at low temperatures and is not prone to brittle cracking; under extreme low temperature conditions of -20°C, the molecular chain segment movement of epoxy resin slows down, but thanks to its high cross-linking density and good intermolecular forces, the coating can still maintain structural integrity and functionality, ensuring the reliability and durability of the coating in low temperature environments in the application of outdoor structures such as high-speed railways, landscape bridges, and petrochemical tanks. In the preparation process of super-weather-resistant antifouling coatings, defoamers effectively control and eliminate bubbles generated during the preparation process by reducing the surface tension of the coating system, avoiding affecting the uniformity and integrity of the coating, resulting in coating appearance defects, reducing the protective performance of the coating, and shortening the service life. Leveling agents can improve the fluidity and self-leveling ability of coatings, reduce the unevenness of coating surface, improve the smoothness and glossiness of coatings, and thus improve the appearance and protective performance of coatings. Good leveling properties can help reduce construction difficulty and improve construction efficiency.
[0020] The high specific surface area and porous structure of mesoporous silica provide a carrier effect in the coating. The physical barrier effect of mesoporous silica also improves the anti-fouling property of the coating. The grafted molybdenum disulfide-aminopropylheptyl-cage polysilsesquioxane is loaded to improve its dispersibility and stability in the coating; the loaded mesoporous silica reduces the spreading of water on the coating surface, making it difficult for water droplets to stay on the coating surface, thereby slowing down the formation of ice layer. The present invention utilizes gamma-glycidyloxypropyltrimethoxysilane to modify molybdenum disulfide, and the silanol groups generated by silane hydrolysis react with hydroxyl groups on the surface of molybdenum disulfide particles to form stable covalent bonds, and at the same time, the silanol groups between silane molecules condense with each other to form a membrane with a network structure that covers the surface of molybdenum disulfide, so that the molybdenum disulfide powder is organic, exhibits anti-agglomeration property in the coating, thereby enhancing its dispersibility and stability in the coating, and adding it to the coating also improves the weather resistance and mechanical properties of the coating; the coating layer with the modified molybdenum disulfide added is smoother, indicating that the dispersibility of the modified molybdenum disulfide is significantly improved, and no agglomeration phenomenon occurs, and the improvement of compatibility has a beneficial effect on the subsequent carrier adsorption step. The modified molybdenum disulfide is further grafted with aminopropylheptyl-cage polysilsesquioxane to obtain loaded mesoporous silica in the carrier, so that the carrier is more dispersed in the coating, and the water barrier effect is enhanced. In addition, the siloxane structure of aminopropylheptyl-cage polysilsesquioxane itself is hydrophobic, and its low surface energy can migrate to the coating surface, making the coating surface denser and further improving the hydrophobic performance. Aminopropylheptyl-cage polysilsesquioxane is a cage structure with an inorganic core composed of a silicon-oxygen skeleton. It is essentially a hybrid molecule, whose core is inorganic silsesquioxane, and the cage corner is an organic n-phenylaminopropyl. The amino group of aminopropylheptyl-cage polysilsesquioxane is grafted with modified molybdenum disulfide to form a stable chemical bond, and then adsorbed with inorganic mesoporous silica, solving the problems of agglomeration of inorganic particles and weak binding force at the two-phase interface, improving bioavailability and making it easier to prepare loaded mesoporous silica. The loaded modified molybdenum disulfide provides low friction properties for the layered structure, which helps to reduce the adhesion of ice layers, thereby improving anti-icing properties. The loaded mesoporous silica also enhances the photochemical stability of the coating due to the addition of modified molybdenum disulfide and aminopropylheptyl-cage polysilsesquioxane, which may reduce damage by absorbing ultraviolet rays. Mesoporous silica provides a better barrier effect for the coating, reduces ultraviolet penetration, and delays aging; the hydrophobicity and low surface energy of aminopropylheptyl-cage polysilsesquioxane contribute to a smooth and dense coating surface, which is not conducive to ultraviolet adsorption and enhances anti-ultraviolet performance, thereby extending the service life of the coating and helping to improve the weather resistance of the coating.
[0021] Beneficial effects of the present invention:
[0022] Compared with the prior art, the super weather-resistant antifouling coating of the present invention solves the problems of carrier agglomeration and compatibility of each component through the combined use of multiple components, strengthens the interfacial bonding force of the coating, thereby improving the bioavailability and overall performance of the coating. It not only performs outstandingly in anti-icing, hydrophobicity, and anti-fouling, but also has significant advantages in weather resistance, mechanical properties and resistance to ultraviolet aging. It extends the service life of the coating in practical applications and meets the long-term protection needs of outdoor structures such as high-speed railways, landscape bridges, and petrochemical tanks under extreme climatic conditions. DETAILED DESCRIPTION
[0023] The parameters of the specific chemical substances used in the examples are from the following sources:
[0024] Epoxy resin: The manufacturer is Guangzhou WeiChuang High-tech Materials Technology Co., Ltd., and the brand name is E-54.
[0025] Polydimethylsiloxane: viscosity (25℃) is 500cp, Laizhou Wantai Silicon Technology Co., Ltd.
[0026] Polyether modified silicone leveling agent: The manufacturer is Tianjin Shengsheng Technology Development Co., Ltd., and the model is SSL-311.
[0027] Curing agent: The manufacturer is Shanghai Yaoshan Industrial Co., Ltd., the product number is YS-1593.
[0028] Molybdenum disulfide: particle size is 20μm.
[0029] Mesoporous silica: pore size is 2-3nm, particle size is 200nm, specific surface area is 200-450m 2 / g, the manufacturer is Beijing Bailingwei Technology Co., Ltd., and the product number is 2748694.
[0030] Aminopropylheptyl-cage polysilsesquioxane: CAS number is 444315-15-5.
[0031] PSS-[3-(2-aminoethyl)amino]propyl-substituted heptaisobutyl: CAS number is 444315-16-6.
[0032] Anilinepropyl caged silsesquioxane: CAS number is 1708993-28-5, the manufacturer is Forsman Technology (Beijing) Co., Ltd., model number is 9502027.
[0033] γ-Glycidyloxypropyltrimethoxysilane: CAS number is 2530-83-8.
[0034] Example 1
[0035] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0036] (1) adding 25 g of molybdenum disulfide to 300 g of 25 wt% ammonia solution, stirring at room temperature for 1 hour to obtain a dispersion, adding 5 g of γ-glycidyloxypropyltrimethoxysilane, stirring at 60° C. for 8 hours, filtering, and vacuum drying at 80° C. to obtain modified molybdenum disulfide;
[0037] (2) 20 g of modified molybdenum disulfide, 40 g of aminopropylheptyl-cage polysilsesquioxane, 8 g of dicyclohexylcarbodiimide, and 4 g of phenyltrimethylammonium chloride were added to 2000 g of N,N-dimethylformamide, and 2000 g of mesoporous silica was added. The mixture was stirred at 130° C. for 24 hours, filtered, and the filter cake was washed with anhydrous ethanol for 3 times. The filter cake was dried under vacuum at 60° C. to obtain the loaded mesoporous silica.
[0038] (3) 1500 g of epoxy resin, 2000 g of loaded mesoporous silica, 15 g of polydimethylsiloxane, and 15 g of polyether-modified silicone leveling agent were sequentially added to 1400 g of anhydrous ethanol, stirred at room temperature for 1 hour, 500 g of curing agent was added, and ultrasonic dispersion was performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0039] Comparative Example 1
[0040] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0041] (1) adding 25 g of molybdenum disulfide to 300 g of 25 wt% ammonia solution, stirring at room temperature for 1 hour to obtain a dispersion, adding 5 g of γ-glycidyloxypropyltrimethoxysilane, stirring at 60° C. for 8 hours, filtering, and vacuum drying at 80° C. to obtain modified molybdenum disulfide;
[0042] (2) 20 g of modified molybdenum disulfide, 40 g of PSS-[3-(2-aminoethyl)amino]propyl-substituted heptaisobutyl, 8 g of dicyclohexylcarbodiimide, and 4 g of phenyltrimethylammonium chloride were added to 2000 g of N,N-dimethylformamide, and 2000 g of mesoporous silica was added. The mixture was stirred at 130° C. for 24 hours, filtered, and the filter cake was washed with anhydrous ethanol for 3 times. The filter cake was dried under vacuum at 60° C. to obtain the loaded mesoporous silica.
[0043] (3) 1500 g of epoxy resin, 2000 g of loaded mesoporous silica, 15 g of polydimethylsiloxane, and 15 g of polyether-modified silicone leveling agent were sequentially added to 1400 g of anhydrous ethanol, stirred at room temperature for 1 hour, 500 g of curing agent was added, and ultrasonic dispersion was performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0044] Comparative Example 2
[0045] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0046] (1) adding 25 g of molybdenum disulfide to 300 g of 25 wt% ammonia solution, stirring at room temperature for 1 hour to obtain a dispersion, adding 5 g of γ-glycidyloxypropyltrimethoxysilane, stirring at 60° C. for 8 hours, filtering, and vacuum drying at 80° C. to obtain modified molybdenum disulfide;
[0047] (2) 20 g of modified molybdenum disulfide, 40 g of aniline propyl caged silsesquioxane, 8 g of dicyclohexylcarbodiimide, and 4 g of phenyltrimethylammonium chloride were added to 2000 g of N,N-dimethylformamide, and 2000 g of mesoporous silica was added. The mixture was stirred at 130° C. for 24 hours, filtered, and the filter cake was washed with anhydrous ethanol for 3 times. The filter cake was dried under vacuum at 60° C. to obtain the loaded mesoporous silica.
[0048] (3) 1500 g of epoxy resin, 2000 g of loaded mesoporous silica, 15 g of polydimethylsiloxane, and 15 g of polyether-modified silicone leveling agent were sequentially added to 1400 g of anhydrous ethanol, stirred at room temperature for 1 hour, 500 g of curing agent was added, and ultrasonic dispersion was performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0049] Example 2
[0050] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0051] (1) adding 25 g of molybdenum disulfide to 300 g of 25 wt% ammonia solution, stirring at room temperature for 1 hour to obtain a dispersion, adding 5 g of γ-glycidyloxypropyltrimethoxysilane, stirring at 60° C. for 8 hours, filtering, and vacuum drying at 80° C. to obtain modified molybdenum disulfide;
[0052] (2) 1500 g of epoxy resin, 1940 g of mesoporous silica, 20 g of modified molybdenum disulfide, 40 g of aminopropylheptyl-cage polysilsesquioxane, 15 g of polydimethylsiloxane, and 15 g of polyether-modified silicone leveling agent are sequentially added to 1400 g of anhydrous ethanol, stirred at room temperature for 1 hour, 500 g of curing agent is added, and ultrasonic dispersion is performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0053] Example 3
[0054] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0055] (1) adding 25 g of molybdenum disulfide to 300 g of 25 wt% ammonia solution, stirring at room temperature for 1 hour to obtain a dispersion, adding 5 g of γ-glycidyloxypropyltrimethoxysilane, stirring at 60° C. for 8 hours, filtering, and vacuum drying at 80° C. to obtain modified molybdenum disulfide;
[0056] (2) Add 40 g of modified molybdenum disulfide to 2000 g of N,N-dimethylformamide, add 2000 g of mesoporous silica, stir at 130 ° C for 24 hours, filter, wash the filter cake three times with anhydrous ethanol, and vacuum dry at 60 ° C to obtain loaded mesoporous silica;
[0057] (3) 1500 g of epoxy resin, 2000 g of loaded mesoporous silica, 15 g of polydimethylsiloxane, and 15 g of polyether-modified silicone leveling agent were sequentially added to 1400 g of anhydrous ethanol, stirred at room temperature for 1 hour, 500 g of curing agent was added, and ultrasonic dispersion was performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0058] Comparative Example 3
[0059] A method for preparing a super weather-resistant antifouling coating comprises the following steps:
[0060] 1500g of epoxy resin, 2000g of mesoporous silica, 15g of polydimethylsiloxane and 15g of polyether-modified silicone leveling agent were sequentially added to 1400g of anhydrous ethanol, stirred at room temperature for 1 hour, 500g of curing agent was added, and ultrasonic dispersion was performed for 20 minutes to obtain the super weather-resistant antifouling coating.
[0061] Example 4
[0062] Application of a super weather-resistant antifouling coating:
[0063] The super weather resistant antifouling coating obtained by the preparation method of Example 1-3 and Comparative Example 1-3 was sprayed on the surface of a 10 cm × 10 cm steel material. The steel material was selected as a Q235A steel plate with a thickness of 2 mm. It was cured at 25°C for 30 minutes and at 300°C for 10 minutes to obtain the steel material coated with the super weather resistant antifouling coating of Example 1-3 and Comparative Example 1-3, and the coating thickness was 50 μm.
[0064] Test Example 1
[0065] Anti-icing test
[0066] The steels coated with the super-weather resistant antifouling coatings of Examples 1-3 and Comparative Examples 1-3 obtained in the application method of Example 4 were placed in environments of -20°C, -10°C, and -5°C, respectively, and the freezing time at different temperatures was recorded. When an ice layer appeared, it was judged as freezing. The humidity of the refrigerator was 79%. The longer the freezing time, the higher the environmental adaptability and the better the anti-icing property of the coating surface. The data are summarized in Table 1.
[0067] Table 1 Anti-icing test
[0068]
[0069]
[0070] Modified molybdenum disulfide is added to the above-mentioned Examples 1-3 and Comparative Examples 1-2. Molybdenum disulfide itself has excellent lubricity and wear resistance. By reducing the friction coefficient of the coating surface, it is more difficult for water droplets to adhere to the surface, which indirectly helps to slow down the formation of ice layers, making the anti-icing property higher than that of Comparative Example 3 without adding molybdenum disulfide. The difference between Example 1 and Example 2 lies in the order and timing of adding modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, and mesoporous silica. Example 1 compounds the three. First, molybdenum disulfide is modified with γ-glycidyloxypropyltrimethoxysilane to form a stable covalent bond connection, which not only improves the dispersibility and compatibility of molybdenum disulfide; aminopropylheptyl-cage polysilsesquioxane, as a special siloxane, has good hydrophobic properties, which helps to reduce the adsorption of water on the coating surface, slow down the formation of ice layers, and the modified molybdenum disulfide. Molybdenum disulfide and amino groups of aniline propyl cage silsesquioxane are grafted to form stable covalent bonds. Dicyclohexylcarbodiimide and phenyltrimethylammonium chloride serve as crosslinkers and surfactants to enhance the adhesion and surface tension of the coating, promote the smooth reaction, further enhance the hydrophobicity and compatibility, and thus improve the anti-icing performance. Finally, it is adsorbed on a mesoporous silica carrier. The high specific surface area and porous structure of mesoporous silica can provide a large number of micropores, which are beneficial to the dispersion and fixation of modified molybdenum disulfide-aniline propyl cage silsesquioxane, and it can be added to the coating to play a more stable overall role. In Example 2, only modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, and mesoporous silica are added separately, which not only fails to solve the dispersibility problem of modified molybdenum disulfide, but also the adsorption priority of mesoporous silica to the two cannot be judged. It can be judged from the experimental data that the freezing time of Example 2 is shorter than that of Example 1, which is judged to be that mesoporous silica preferentially adsorbs modified molybdenum disulfide, resulting in low utilization rate of the added aminopropylheptyl-cage polysilsesquioxane, proving that single addition cannot achieve the composite addition effect of Example 1. In Example 3, only modified molybdenum disulfide was added to be adsorbed on the mesoporous silica carrier, and special components such as aminopropylheptyl-cage polysilsesquioxane were lacking. The hydrophobicity and surface activity of the coating were relatively weak, so the anti-icing performance in a low-temperature environment was not as good as that of Examples 1-2. The cost of aminopropylheptyl-cage polysilsesquioxane was high, so no experiments were conducted on the adsorption of mesoporous silica by modified molybdenum disulfide and aminopropylheptyl-cage polysilsesquioxane alone. Comparative Examples 1-2 screened aminopropylheptyl-cage polysilsesquioxane on the basis of Example 1. Comparative Examples 1-2 replaced the amino-containing PSS-[3-(2-aminoethyl)amino]propyl-substituted heptaisobutyl and anilinepropyl cage polysilsesquioxane respectively. The anti-icing technical effect was lower than that of Example 1 at -20°C, -10°C, and -5°C. The possible reason lies in the grafting rate with modified molybdenum disulfide. If the grafting rate is low, the pores of the mesoporous silica adsorb unreacted modified molybdenum disulfide, resulting in low overall anti-icing properties.Therefore, the anti-icing technology of Example 1 has the best effect.
[0071] Test Example 2
[0072] Aging test
[0073] The steel coated with the super-weather resistant antifouling coatings of Examples 1-3 and Comparative Examples 1-3 obtained in the application method of Example 4 was subjected to an aging resistance test. The test was based on method B of the national standard GB / T23987-2009 "Artificial weathering aging of paint and varnish coatings - exposure to fluorescent ultraviolet light and water", and the irradiation and spraying steps were cyclically performed until the coating surface seemed to change color and age, and the time when aging occurred was recorded. The data are summarized as described in Table 2.
[0074] Table 2 Aging resistance test results
[0075] Time of discoloration and aging Example 1 2870h Example 2 2105h Example 3 1785h
[0076] In test example 2, the ultraviolet aging resistance test was performed on the ultraviolet aging resistance test of the super-weather resistant antifouling coatings of Examples 1-3, among which the aging resistance time of Example 1 was the longest. The difference was that the aminopropylheptyl-cage polysilsesquioxane contained in the mesoporous silica loaded in Example 1 had good ultraviolet resistance. This cage-shaped siloxane could absorb and disperse ultraviolet rays, reducing direct damage to the coating. The addition of modified molybdenum disulfide was used to improve the adsorption and dispersion of aminopropylheptyl-cage polysilsesquioxane in mesoporous silica. While Example 2 only added modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, and mesoporous silica separately, and the technical effect of adding separately was lower than that of Example 1. The ultraviolet resistance of the loaded mesoporous silica added in Example 3 was weak, and the lack of aminopropylheptyl-cage polysilsesquioxane, a siloxane with a special structure, resulted in a decrease in the absorption and dispersion ability of the coating to ultraviolet rays. Therefore, the super-weather resistant antifouling coating of Example 1 has a certain ultraviolet aging resistance technical effect.
[0077] Test Example 3
[0078] Stain resistance test
[0079] The super-weather resistant antifouling coatings of Examples 1-3 and Comparative Examples 1-3 were sprayed onto standard horse mouth boards and cured to obtain test samples, and 3 test samples were prepared for each group; the test was conducted according to Method A of the national standard GB / T9780-2013 "Test Method for Stain Resistance of Architectural Coatings", and the test stain was a mixture of vaseline and carbon black; the test used five grades from 0 to 4 to evaluate the test results, which corresponded to five grades of 5, 4, 3, 2, and 1 of the basic gray card (GB / T 250); two tested coating test plates were taken from each Example and Comparative Example, and the colorimetric evaluation grade was compared with an untested coating test plate according to the color difference between the conventional colorimetric box and the basic gray card in 8.2b item of GB / T 9761-2008; the data were summarized as described in Table 3, and the evaluation grade was based on that described in Table 4.
[0080] Table 3 Determination results of stain resistance
[0081] Stain resistance grade / level Example 1 0 Comparative Example 1 2 Comparative Example 2 2 Example 2 2 Example 3 2 Comparative Example 3 3
[0082] Table 4 Rating levels
[0083]
[0084]
[0085] In Test Example 3, only Example 1 received a grade 0 rating in the stain resistance test, indicating that the surface of the coating has better stain resistance. The hydrophobicity of aminopropylheptyl-cage polysilsesquioxane in the loaded mesoporous silica provides a physical barrier for the coating, making it difficult for aqueous and oily stains to spread and penetrate on the coating surface, thereby reducing the adsorption of stains. The addition of modified molybdenum disulfide enhances the smoothness and anti-adhesion ability of the coating, reduces the friction between the stains and the coating, makes the stains easier to remove and less likely to leave traces, thereby reducing the adhesion of stains. The high porosity structure of the mesoporous silica adsorbs and fixes the two, which work together to improve the stain resistance of the coating, so that the coating can effectively resist stains and maintain surface cleanliness. The stain resistance level of Examples 2-3 and Comparative Examples 1-2 are both Level 2, and the coating's stain resistance is lower than that of Example 1, proving that the steps for adding each component in the loaded mesoporous silica and the formulation will affect the overall anti-fouling property, and not any type of siloxane can achieve the same effect when used in combination; and Comparative Example 3 lacks modified molybdenum disulfide, and may not be as good as other examples in terms of coating surface smoothness and anti-adhesion ability, showing moderate pollution and color difference.
[0086] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a super weather-resistant antifouling coating, characterized in that: The following steps are involved: (1) adding molybdenum disulfide to an aqueous ammonia solution, stirring at room temperature for 1-2 hours to obtain a dispersion, adding γ-glycidyloxypropyltrimethoxysilane, stirring at 50-60° C. for 8-10 hours, filtering, and vacuum drying at 60-80° C. to obtain modified molybdenum disulfide; (2) adding modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, dicyclohexylcarbodiimide, and phenyltrimethylammonium chloride to N,N-dimethylformamide, adding mesoporous silica, stirring at 120-140° C. for 12-24 hours, filtering, washing the filter cake with anhydrous ethanol for 2-4 times, and vacuum drying at 50-60° C. to obtain loaded mesoporous silica; (3) adding epoxy resin, loaded mesoporous silica, defoaming agent and leveling agent to anhydrous ethanol in sequence, stirring at room temperature for 1-2 hours, adding curing agent, and ultrasonically dispersing for 10-30 minutes to obtain the super weather-resistant antifouling coating.
2. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: The ammonia solution in step (1) is a 20-25 wt % ammonia solution.
3. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: In the step (1), the weight ratio of molybdenum disulfide, ammonia solution and γ-glycidyloxypropyltrimethoxysilane is 2-3:20-30:0.4-0.
6.
4. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: In the step (2), the weight ratio of modified molybdenum disulfide, aminopropylheptyl-cage polysilsesquioxane, dicyclohexylcarbodiimide, phenyltrimethylammonium chloride, N,N-dimethylformamide, and mesoporous silica is 1-3: 3-6: 0.5-1: 0.2-0.6: 180-220: 180-220.
5. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: In the step (3), the weight ratio of epoxy resin, loaded mesoporous silica, defoamer, leveling agent, anhydrous ethanol and curing agent is 140-160:180-220:1-2:1-2:120-160:30-60.
6. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: The pore size of the mesoporous silica in step (2) is 1-5 nm.
7. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: The defoaming agent in step (3) is polydimethylsiloxane.
8. The method for preparing the super weather-resistant antifouling coating according to claim 1, characterized in that: The leveling agent in step (3) is a polyether modified silicone leveling agent.
9. A super weather-resistant antifouling coating, characterized in that: The super weather-resistant antifouling coating is prepared by the preparation method of any one of claims 1 to 8.
Citation Information
Patent Citations
Nanometer coating used for preventing icing of high tension transmission line and application thereof
CN103059650A
High-strength wear-resistant polyurethane composite board and processing technology thereof
CN116872592A
Coating agent for wiper blade rubber and wiper blade rubber
JP2003138216A